PREVALENCE OF LEFT VENTRICULAR HYPERTROPHY (LVH) IN TYPE 2 DIABETES MELLITUS AT PAF HOSPITAL MUSHAF - JABEEN , S; AHMED , A; SHAUKAT , W; TARIQUE , M; HUSSAIN , M; ASGHAR , M (Biological and Clinical Sciences Research Journal, 2024)
Left Ventricular Hypertrophy (LVH) is widely recognized as a predictor of adverse cardiovascular outcomes, including heart failure, arrhythmias, and sudden cardiac death. Objective: The basic aim of the study is to find the prevalence of left ventricular hypertrophy (LVH) in type-II diabetes mellitus at PAF Hospital Mushaf. Methods: This Cross-sectional study was conducted at the Department of Medicine, PAF Hospital Mushaf, Sargodha from January to July 2024. Data were collected through a non-probability, consecutive sampling technique. Data were collected using a self-generated questionnaire and included biodata like age, gender, contact number, and the presence or absence of LVH. Transthoracic 2D Echo was performed in selected individuals on the Toshiba Xario (Echo machine). Results: Data were collected from 154 patients with a mean age of 52.6 ± 7.4 years, with a nearly equal gender distribution, consisting of 48% male and 52% female participants. The average duration of diabetes was 10.3 ± 4.2 years, and the mean BMI was 28.4 ± 3.7 kg/m², indicating a mildly overweight population. Blood pressure was on average 140/90 ± 10/6 mmHg, with a significant proportion (61%) suffering from hypertension. Fasting blood glucose levels were elevated at 175.6 ± 34.8 mg/dL, and the mean HbA1c was 8.5 ± 1.2%, reflecting poor long-term blood sugar control. Conclusion: It is concluded that Left Ventricular Hypertrophy (LVH) is prevalent in a significant proportion of patients with Type 2 Diabetes, particularly those with longer diabetes duration and male gender. The findings highlight the importance of early detection and management of cardiovascular risk factors in diabetic patients and a significant gender difference, with male patients being more likely to develop LVH compared to females in this study were observed.